Makna Balaganjur Dalam Aktivitas Sosial Masyarakat Bali - I Wayan Suharta (Institut Seni Indonesia Denpasar, 2007)
Balaganjur is a form of performance arts and audio- visually it might be an independent art. Balaganjur is a musical communication that instigates sensation and emotional response between the composer, players and viewers. It might influence the fan who are familier with the background of Balinese social life. This article is meant to see and analyze how Balinese people value the function of Balaganjur, especially in the context of festive social activity. The performance of Balaganjur is always conected to a religious life, traditional lore, and aspect of artistic life in response to the development of the cultural millie. Generally, Balaganjur complements the implementation of religious ritual. However, when Balaganjur is secularly composed and performed as an aesthetic presentation, Balaganjur develops its function toward profan values.